The Astronomer of Vilnius. The Correspondence of Marcin Poczobut-Odlanicki and Adam Naruszewicz - Kaliszewski, Wojciech (Senoji Lietuvos literatūra, 2021)
The article presents the correspondence between Marcin Poczobut-Odlanicki, rector of Vilnius Academy, a Catholic priest, astronomer, scholar, and reformer, and Adam Naruszewicz, a poet and one of the most significant figures of the cultural life in the Polish-Lithuanian Commonwealth under the reign of King Stanisław August Poniatowski. Poczobut approached Naruszevicz, with whom he had been friends since his Jesuit days, to ask for support for his research initiatives. He presented very interesting and important plans of establishing the Scientific Society, the main goal of which would be the dissemination of knowledge. The preserved letters show the astronomer of Vilnius as a broad-minded person, a curious scholar, and a capable organiser of research. The correspondence also reveals the bonds of friendship between Naruszewicz and Poczobut. This epistolary legacy and its discussion enrich our knowledge of the culture of the Age of Enlightenment in the Polish-Lithuanian Commonwealth.